Radical voices, radical ways : articulating and disseminating radicalism in seventeenth- and eighteenth-century Britain - Curelly, Laurent; Smith, Nigel, 1958- (Seventeenth- and eighteenth-century studies., 2016)
This edited collection addresses the issue of radicalism by focusing on the media that contributed to its diffusion in the early modern era, using innovative interdisciplinary research that draws on a wide range of primary material.